The Association Between Radioiodine Refractory in Papillary Thyroid Carcinoma, Sodium/Iodide Symporter Expression, and BRAFV600E Mutation - Anekpuritanang, Tauangtham; Uataya, Maythad; Claimon, Apichaya; Laokulrath, Natthawadee; Pongsapich, Warut; Pithuksurachai, Paveena (OncoTargets and therapy, 2021)
Objective: To study the association between radioiodine refractory papillary thyroid carcinoma, sodium/iodide symporter (NIS) expression, and the BRAFV600E mutation. Methods: A study was conducted on 30 radioiodine refractory papillary thyroid carcinoma patients and 30 radioiodine-avid papillary thyroid carcinoma patients. The expressions of sodium/iodide symporter and BRAFV600E mutated protein were determined by immunohistochemistry using formalin-fixed, paraffin-embedded tissue. Results: The mutated BRAFV600E protein was identified in 26 radioiodine refractory papillary thyroid carcinoma subjects (86.7%) and 22 radioiodine-avid papillary thyroid carcinoma subjects (73.3%), with no significant difference between the 2 groups (P = 0.3). Sodium/iodide symporter expression was detected in 4 of 30 cases (13.3%) from the radioiodine-avid papillary thyroid carcinoma group but was negative for all radioiodine refractory cases. There was no association between sodium/iodide symporter expression and radioiodine refractory papillary thyroid carcinoma (P = 0.11). Cases with positive NIS expression were likely negative for BRAFV600E mutation (3/4; P = 0.02). Conclusion: Papillary thyroid carcinomas with BRAFV600E mutation were more likely to be negative for NIS expression. BRAFV600E mutation and NIS expressions cannot be used to predict radioiodine sensitivity.